Efficient wireless power transfer via magnetic resonance coupling using automated impedance matching circuit - Ali, Esraa Mousa; Alibakhshikenari, Mohammad; Virdee, Bal Singh; Soruri, Mohammad; Limiti, Ernesto (MDPI, 2021)
In this paper, an automated impedance matching circuit is proposed to match the impedance of the transmit and receive resonators for optimum wireless power transfer (WPT). This is achieved using a 2D open-circuited spiral antenna with magnetic resonance coupling in the low-frequency ISM band at 13.56 MHz. The proposed WPT can be adopted for a wide range of commercial applications, from electric vehicles to consumer electronics, such as tablets and smartphones. The results confirm a power transfer efficiency between the transmit and receive resonant circuits of 92%, with this efficiency being sensitive to the degree of coupling between the coupled pair of resonators.